The miraculuous water of Guðmundr Arason and the limits of holiness in medieval Iceland - Anderson, Joel 1982- (2008)
The aim of this thesis is to investigate the ways in which Guðmundr’s fourteenth century hagiographers – particularly the redactors of Guðmundar saga B and Guðmundar saga D – incorporated the theme of Guðmundr’s holy water into their hagiographies. How did they justify and present Guðmundr’s water consecrations as righteous and holy? To what extent could they claim the holiness of wells and springs in far-flung locations throughout Iceland blessed by a charismatic and controversial priest / bishop? How did they deal with the doubts and criticisms leveled against Guðmundr’s water? How did they portray Guðmundr’s water as miraculous? After surveying Guðmundr’s biography and the sources for his life, I will discuss the hagiographic and (potentially) historical dimensions of Guðmundr’s water consecrations. I will then consider attitudes towards the miraculous in medieval Iceland and how these attitudes relate to Guðmundr’s water. After briefly outlining the scope and variety of Guðmundr’s water miracles, I will expound on the ways in which the hagiographers dealt with and explained particular aspects of Guðmundr’s miraculous powers. In the second half of this thesis, I will discuss specific episodes and passages that were added to the B and D redactions of Guðmundr’s vita in an attempt to justify his miraculous water consecrations. Lastly, I will address three separate episodes of doubt surrounding Guðmundr’s water in the hagiographies, examining how these episodes do and do not allay the concerns and questions about the expansive limits within which Guðmundr and his hagiographers claimed holiness. Norwegian Fulbright Foundation, The Icelandic Ministry of Education